Synthesis and Characterization of Some New Metals Complexes of ((4 Methoxy Benzoyl) Carbamothioyl) Glycine - Raghad Abdulsattar, Basima M. Sarhan (Pakistan Journal of Medical & Health Sciences, 2022)
A new ligand ( 4- methoxy benzoyl ) carbamothioyl ) Glycine (MCG) is synthesized by reaction of (4- methoxy benzoyl isothiocyanate) with Glycine(1:1). It is characterized by micro elemental analysis (C.H.N.S.), FT-IR, (UV-Vis) and 1H and 13CNMR spectra. Some metals ions complexes of this ligand were prepared and characterized byFT-IR,UV-Visible spectra, conductivity measurements, magnetic susceptibility and atomic absorption. From results obtained, the following formula [M(MCG)2] where M2+ = Mn, Co, Ni, Cu, Zn, , Cd and Hg, the proposed molecular structure for these complexes as tetrahedral geometry, except copper complex is has square planer geometry